(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Non-biodegradable wastes materials pose a significant environmental hazard to living organisms and their disposal requires effort, time and money. One of the most useful processes by which this waste can be exploited is the recycling process. Iron filings are one of the wastes materials that can be recycled and used in engineering fields. One of these is the use of the process in construction. Iron filings are very small pieces of iron that look like a light powder. They are very often used in science demonstrations to show the direction of a magnetic field. The purpose of this project is to evaluate the possibility of using iron filings as one of the component of concrete mix. Three different percentage of iron filings were added to concrete mix to measure the variation, which may be obtained in compression and tensile concrete strengths after 28 days. 45 of 150mm cubes and prisms of 100x100x400mm were performed and tested in this study using 0% (control), 5%, 10% and 15% of iron filing in concrete mix.